Russia and Financial World: on the Threshold of System Transformations - A. V. Kuznetsov (Проблемы постсоветского пространства)
The modern global financial system is based on unlimited dollar issuance, which is backed by a key reserve asset – US debt obligations. The concept of official foreign exchange reserves promoted by the IMF puts in a privileged position the countries with reserve currencies, primarily the United State. This concept has exhausted the possibilities for productive investment of the savings of the rest of the world. As a result, the savings of the periphery of the global economy are directed to the consumption and speculative spheres. Global financial crises has proved – despite speculative activities banks have priority support from key central banks. Developing countries objectively claim a parity distribution of the benefits and costs of financial globalization, as they play an increasingly important role in global value chains. As a donor of the global financial system, Russia is practically not involved in the distribution of profits in the global financial market. As the largest supplier of raw materials, intellectual and financial resources, Russia requires new solutions in the field of international monetary circulation.